2019
DOI: 10.5922/2079-8555-2019-1-1
|View full text |Cite
|
Sign up to set email alerts
|

The resistance of the greater Baltic region states to market cycle changes

Abstract: A non-linear change process is a specific feature of a poorly regulated market economy. However, many researchers have shown that different economic sectors do not respond to market cycles in a similar way. Regional economic systems are a combination of many sectors, therefore a hypothesis about the correlation between the stability of regional economies and market cycles is examined. The study is conducted using the Baltic countries (hereinafter referred to as Greater Baltic Region, GBR) as an example. GBR co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Based on the analyses of the dynamics of GDP and its components, the patterns of development and economy growth, cycles and resistance of different economies to them become apparent. Thus, (Baburin, 2019) researched the resilience of the economies of the Greater Baltic Region to the cycles` conditions, calculated the cycle duration of 5-7 years and indicated that the main factor of stability of a country is its specialization. In their works (Korotayev et al, 2020) studied Kondratiev's long waves based on growth rates of global GDP and concluded that it is the developing countries that are generating such waves during the given period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the analyses of the dynamics of GDP and its components, the patterns of development and economy growth, cycles and resistance of different economies to them become apparent. Thus, (Baburin, 2019) researched the resilience of the economies of the Greater Baltic Region to the cycles` conditions, calculated the cycle duration of 5-7 years and indicated that the main factor of stability of a country is its specialization. In their works (Korotayev et al, 2020) studied Kondratiev's long waves based on growth rates of global GDP and concluded that it is the developing countries that are generating such waves during the given period.…”
Section: Literature Reviewmentioning
confidence: 99%